A First Report of Variscite Tairona Artifacts (A.D. 1100-1600) from the Sierra Nevada de Santa Marta, Colombia, and Its Implications for Precolumbian exchange Networks in the Region. Issue 4 (December 2016) - Acevedo, Natalia; Weber, Marion; García-Casco, Antonio; Proenza, Joaquín Antonio; Sáenz, Juanita; Cardona, Agustín
Abstract: Archaeometric analyses (Raman Spectroscopy Analysis, X-Ray Diffraction, and Electron Microprobe Analysis) of greenstone beads of the precolumbian Tairona culture (A.D. 1100–1600) of the Sierra Nevada de Santa Marta, Colombia, have revealed that they are made of variscite-group minerals. These beads were curated at the Museo del Oro, Bogotá, and the Archaeology Laboratory of the Universidad del Norte, Barranquilla. Variscite minerals of the variscite-strengite series are rare in nature, and therefore provenance data of source material are useful for the development of intercultural influence models. The abundance of this rare material in prehistoric Colombian collections strongly indicates not only that this material had important symbolic and prestige value for ancient Tairona societies (Nahuange and Tairona periods) but also that these societies participated in ancient trade routes, including, at least, the Andes of present-day Colombia and Venezuela, and the southern Caribbean coast.